Large‐Scale Parallel Surface Functionalization of Goblet‐type Whispering Gallery Mode Microcavity Arrays for Biosensing Applications. Issue 19 (2nd July 2014) - Bog, Uwe; Brinkmann, Falko; Kalt, Heinz; Koos, Christian; Mappes, Timo; Hirtz, Michael; Fuchs, Harald; Köber, Sebastian
<x xml:space="preserve">Abstract</x> A novel surface functionalization technique is presented for large‐scale selective molecule deposition onto whispering gallery mode microgoblet cavities. The parallel technique allows damage‐free individual functionalization of the cavities, arranged on‐chip in densely packaged arrays. As the stamp pad a glass slide is utilized, bearing phospholipids with different functional head groups. Coated microcavities are characterized and demonstrated as biosensors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>